The development of psychometric scales to measure sense of place - Bott, Suzanne Elizabeth, author; Haas, Glenn E., advisor; Lakey, Jeff, committee member; Banning, James H., committee member; Wells, Marcella, committee member (Colorado State University. Libraries, 2000)
Sense of place has been described as a subjective construct without a formalized definition or set of determining criteria. Recent research has expressed a need for a more holistic approach to designing and managing landscapes (Driver et al. 1996). This research set out to 1) develop a simplified definition of sense of place and 2) test domains and scales evaluating factors influencing sense of place perception. Colorado State University in Fort Collins, Colorado was the research setting. Two sites previously determined to have high and low sense of place (Greene 1996b) were evaluated. One was the Oval, a historic mall with significant vegetation and regional vernacular architecture; the other was a plaza with modem architecture, nonnative building materials, and limited vegetation. The methodology involved multitrait-multimethod social science techniques based on grounded theory and qualitative research, and quantitative empirical survey research. Steps included a literature review of Environmental Psychology, Geography, Environmental Design, and Resource Management research. Focus groups and an expert panel developed 90 items to be used in a written survey to evaluate sense of place, grouped into two sets of factors, four general groups (domains), and fifteen subgroups (scales). Three qualitative questions were included that asked respondents to describe specific places and emotions that came to mind when thinking about sense of place. In addition to testing the scales at two different sites, the survey used two different experimental methods to test for differences between multisensory on-site perception and single-sense visual perception. Surveys were completed by 373 students from the College of Natural Resources during July and August 1999. Reliability and correlation analysis verified reliability of the domains and scales. Factor analysis resulted in no additional scales. Analysis of Variance showed significant differences between the two sites and the two methods of evaluation. Thematic analysis of qualitative data determined additional factors to enrich the quantitative data. The study resulted in significant findings in four areas: 1) a simplified interdisciplinary definition of sense of place: sense of place is the perception of meaning associated with a site; 2) a set of psychometric domains, scales, and items were developed and tested; 3) significant differences were found between two different experimental methods and two different settings; and 4) a new holistic model was proposed in contrast to the linear design of previous models. The research supports and unites literature and practice from four disciplines which have previously worked independently to generate place perception theory. This research takes a significant step toward understanding human-environment interaction by providing a bridge between the theoretical and applied processes. The research supports individual perceptions as valid, shows that sense of place is a concrete phenomenon which can be assessed objectively, and provides a methodology to objectively evaluate sense of place.
Keywords: environmental science; area planning and development; geography; psychological tests; quantitative psychology